Epithelial-To-Mesenchymal Transition and Migration of Human Peritoneal Mesothelial Cells Undergoing Senescence. Issue 1 (January 2019) - Kawka, Edyta; Witowski, Janusz; Sandoval, Pilar; Rudolf, Andras; Vidal, Angela Rynne; Cabrera, Manuel Lopez; Jörres, Achim
Background: Epithelial-to-mesenchymal transition (EMT) of human peritoneal mesothelial cells (HPMCs) contributes to fibrotic thickening of the peritoneum that develops in patients on peritoneal dialysis (PD). The process is thought to be largely mediated by transforming growth factor-beta (TGF-β). As TGF-β has also been implicated in senescence of HPMCs, we have performed an exploratory study to examine if senescent HPMCs can undergo EMT. Methods: Omentum-derived HPMCs were rendered senescent by repeated passages in culture. Features of EMT were assessed by immunostaining and quantitative polymerase chain reaction (qPCR) at various stages of the HPMC lifespan and after treatment with or without TGF-β. The motility of HPMCs was assessed in a scratch wound migration assay. Results: Replicative senescence of HPMCs was associated with a gradual increase in the constitutive expression of EMT markers, including increased production of extracellular matrix proteins. However, senescent HPMCs also retained epithelial cell features such as cytokeratin, calretinin, and E-cadherin and showed decreased, rather than increased, motility. In contrast, exposure to TGF-β resulted in an up-regulation of mesenchymal markers and down-regulation of epithelial markers. Such effects of TGF-β occurred both in young and senescent cells, although they were less pronounced in senescence. Conclusions: Senescence of HPMCs is associated with spontaneous development of several EMT features. At the same time, senescent HPMCs preserve epithelial cell-like characteristics and are less prone to develop a full EMT phenotype in response to TGF-β. These observations may support the concept of cellular senescence being antagonistically pleiotropic with regard to EMT.